Multidisciplinary Diagnostic and Therapeutic Approaches in Obesity-Hypoventilation Syndrome-An Updated Review For Radiologists and Respiratory Professionals - Almutairi, Amal Bader; Khawla Yousef Alqallaf; Hend Abdullah Hassan Hassan; Asma Saud Alanazi; Mai Fhaid Alshammari; Amani Mohammed Hassan Sholan; Murdi Ali Naser Al Dawsri; Abdurhman Majed Ali Al Dawsary; Bader Fayz Mohammad Al Dawseri; Misfer Marzoq Mohammad Al Dawseri; Fahad Ali Ali Sharahili; Rahaf Ali Alqahtani (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Obesity-hypoventilation syndrome (OHS) is a complex disorder characterized by daytime hypercapnia, severe obesity, and sleep-disordered breathing. Its pathogenesis involves mechanical respiratory load, impaired ventilatory drive, and neurohormonal dysregulation, often coexisting with obstructive sleep apnea (OSA). <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To provide an updated multidisciplinary review emphasizing diagnostic strategies and evidence-based therapeutic approaches relevant to radiologists, pulmonologists, and sleep specialists. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes current literature on OHS epidemiology, pathophysiology, clinical features, diagnostic modalities, and management, incorporating data on PAP therapy, weight-loss interventions, cardiopulmonary complications, and multidisciplinary care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> OHS is strongly associated with severe obesity and OSA, with significant cardiopulmonary morbidity including pulmonary hypertension and right heart failure. Positive airway pressure (PAP) therapy remains the cornerstone of management, improving gas exchange, reducing hypercapnia, and lowering hospitalization and mortality rates. Weight-loss interventions, including structured programs and bariatric surgery, significantly improve ventilation and OSA severity, though complete resolution is uncommon. Persistent cases may require adjunctive pharmacologic therapy or tracheostomy. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early recognition, structured evaluation, and comprehensive multimodal therapy—including PAP, weight management, and specialist collaboration—are essential to prevent long-term cardiopulmonary complications and optimize outcomes in OHS.